Public motives and willingness to participate in first-in-human clinical trials in Saudi Arabia: A new era in the making. Issue 5 (September 2019) - Almutairi, Adel F.; Almutairi, Badriah M.; Alturki, Abdullah S.; Adlan, Abdallah A.; Salam, Mahmoud; Al-Jeraisy, Majed I; Balkhy, Hanan H.
Abstract: Background: Participation in first-in-human (FIH) clinical trials is a valuable contribution to science. This study aims to investigate the Saudi public's attitude toward FIH clinical trials, identify their willingness to take part in it, and their preferences for participating in these kinds of trials, given the fact that the Saudi FDA has never approved such studies in Saudi Arabia. Methods: This was a cross sectional study conducted in February 2018. It was based on a self-reported survey distributed by convenience among Saudi adults visiting a national festival in Riyadh and through social media. Data were analysed using descriptive and bivariate statistics, as well as linear and binary logistic regression. Results: Study participants who were invited and completed the survey were 657. The percentage mean score of participants' attitudes and concern was 70.1 ± 16.4 and 58.3 ± 15.3 respectively. Almost 71.5% expressed their intention to enroll in such trials. Higher attitudinal scores were reported by those who perceived healthcare services as good/excellent (adj.P < 0.001), and by those who had less concerns (adj.P = 0.005). Less educated participants were 1.75 [1.04–2.93] times more likely to enroll in future clinical trials, adj.P = 0.035. For every one unit increase in the attitudinal score, study participants were 1.03 [1.02–1.04] more likely to enroll in future trials, adj.P < 0.001. In contrary, for every one unit increase in concern scores, the odds of enrollment decreased among study participants by 0.98 [0.97–0.99], adj.P = 0.017. The factors causing people to decline participation were mainly fear of the unknown, social reasons, religious reasons, moral reasons, and the concern over human beings being treated as animals. The preferred duration for participation was 1–3 days (n = 268, 57%). Participants revealed their preferences of clinical trial studies were in favor: (a) vaccines (n = 209, 44.5%); (b) treatment drugs (n = 232, 49.4%); and (c) medical devices (n = 310, 66.0%). Conclusion: The Saudi public community showed a high level of enthusiasm for participation in future FIH clinical trials, yet they had some reservations. Increasing public awareness about the benefits of clinical trials and conduction process helps to alleviate the concerns of the Saudi people and to increase their likelihood of enrollment.